New BODIPYs for photodynamic therapy (PDT): Synthesis and activity on human cancer cell lines. Issue 21 (1st November 2020) - Caruso, Enrico; Malacarne, Miryam C.; Marras, Emanuela; Papa, Ester; Bertato, Linda; Banfi, Stefano; Gariboldi, Marzia B.
Graphical abstract: Abstract: A new class of compounds based on the 4, 4-difluoro-4-bora-3a, 4a-diaza-s-indacene core, known as BODIPYs, has attracted significant attention as photosensitizers suitable for application in photodynamic therapy (PDT), which is a minimally invasive procedure to treat cancer. In PDT the combination of a photosensitizer (PS), light, and oxygen leads to a series of photochemical reactions generating reactive oxygen species (ROS) exerting cytotoxic action on tumor cells. Here we present the synthesis and the study of the in vitro photodynamic effects of two BODIPYs which differ in the structure of the substituent placed on the meso (or 8) position of the dipyrrolylmethenic nucleus. The two compounds were tested on three human cancer cell lines of different origin and degree of malignancy. Our results indicate that the BODIPYs are very effective in reducing the growth/viability of HCT116, SKOV3 and MCF7 cells when irradiated with a green LED source, whereas they are practically devoid of activity in the dark. Phototoxicity occurs mainly through apoptotic cell death, however necrotic cell death also seems to play a role. Furthermore, singlet oxygen generation and induction of the increase of reactive oxygen species also appear to be involved in the photodynamic effect of the BODIPYs. Finally, it is worth noting that the two BODIPYs are also able to exert anti-migratory activity.